Digital educational platforms as a means of preparing future primary school teachers for the organization of distance learning - Knysh, Oryna (ScienceRise: Pedagogical Education, 2026)
The article presents a theoretical substantiation of the impact and promising role of digital educational platforms in the preparation of pre-service teachers for organizing distance learning in the context of educational digitalization. The relevance of the study is driven by the need to update approaches to professional training due to the transformation of the teacher's role, shifting from a mere transmitter of knowledge to a mentor, tutor, and facilitator who assists students in defining their own educational trajectory, as well as changing models of interaction among participants in the educational process. A theoretical analysis of approaches by domestic and foreign scholars toward the concept of "digitalization of education" has been conducted. The study identifies the primary groups of challenges (regulatory, legal, and social) faced by educators when implementing distance learning in primary schools. It is emphasized that for effective interaction with primary school children, a teacher must possess not only technical knowledge and skills in working with educational platforms but also provide psychological support to families and actively interact with parents. The research is based on an analysis of scientific sources, the regulatory framework, and practical experience in using digital educational platforms. The didactic possibilities of synchronous and asynchronous learning forms are outlined. It has been established that educators must expediently combine these forms within the educational process for primary school students. The study analyzes platforms and services that form the basis of synchronous (Zoom, Google Meet) and asynchronous interaction (Blackboard, Google Classroom, Canvas, Edmodo), as well as integrated digital ecosystems (Google Workspace for Education, Microsoft 365 Education). It is concluded that the use of digital educational platforms during the training of pre-service teachers models the conditions of professional activity in primary schools, significantly increasing their level of practical readiness to organize a digital environment for primary students in distance learning conditions